The triple layered business model canvas in smart agriculture: the case of Evja startup - Basile, Vincenzo (Piccola Impresa / Small Business, 2021)
In recent years, the studies of Business Model Innovation (BMI) and Circular Economy (CE) has been an issues much debated in literature. Moreover, the sustainable development enhanced by the Green Economy (GE) and by smart technologies represent a huge opportunity for generating profit in newly and environmentally way. Actually, was not widely investigated, what is the impact of Sustainable Business Model (SBM) in terms of competitive advantage for the firms, especially for Small and medium-sized enterprises (SMEs) towards big companies. The research design is based on the following phases. Firstly, give a literature review of significant and emerging studies on BMI and SBM. In a second step, access to a conceptual and managerial model, in order to compare it in the scientific community and expand the debate on sustainable development also in managerial perspective. The proposed conceptual model has been tested on EVJA company, an Italian innovative start-up operating in agri-food industry. The methodology adopted was a qualitative analysis. Earlier, starting with a deep literature review in order to identify and classify the main contributions on the topic of sustainable and circular business model. Later, by in depth interviews and focus group to a firm’s key informants (namely the CEO and Co-Founder and Chief technology officer and Co-Founder of the firm) and on experts and practitioners deriving from academic and managerial community. The desk research on the case study was enriched by the recurs to primary and secondary sources. The final aim is to suggest a Triple Layered Business Model Canvas (TLBMC), in the reference framework of circular economy, to support the farms manager to figure out appropriate course of actions to promote the re-use and fighting climate changes, providing better services and products (in terms of value for money to the customers). The TLBMC tool in agri-food industries can fostering the SMEs to captures value evaluating the potentials of SBM and producing in a more economically and responsibly way. In a holistic vision, that would be involve its customers, suppliers, employees, and communities, as well as its shareholders.